The analysis of firms and employees : quantitative and qualitative approaches - Bender, Stefan (National Bureau of Economic Research conference report., 2008)
The long-term impact of globalization, outsourcing, and technological change on workers is increasingly being studied by economists. At the nexus of labor economics, industry studies, and industrial organization, The Analysis of Firms and Employees presents new findings about these impacts by examining the interaction between the internal workings of businesses and outside influences from the market using data from countries around the globe. The result is enhanced insight into the dynamic interrelationship between firms and workers. A distinguished team of researchers here examines the relati.